Macroscopic alignment of chromonic liquid crystals using patterned substrates. Issue 15 (30th March 2016) - Kim, Jeong Yeon; Nayani, Karthik; Jeong, Hyeon Su; Jeon, Hwan-Jin; Yoo, Hae-Wook; Lee, Eun Hyung; Park, Jung Ok; Srinivasarao, Mohan; Jung, Hee-Tae
Abstract : Stable alignment of lyotropic chromonic liquid crystals (LCLCs) is demonstrated, along with an explanation of why such alignment has been difficult. Abstract : We demonstrate an efficient technique to align lyotropic chromonic liquid crystals (LCLCs) using secondary sputtering lithography (SSL). Monodomains of LCLCs prepared using SSL maintained their stable alignment for days. A generalization of Berreman's theory was employed to determine the anchoring strength of LCLCs on tessellated surface patterns. The anchoring energy initially increases with the amplitude ( A ) of the grooves and excellent alignment of LCLCs was observed when the amplitude of the grooves is equal to half its wavelength ( λ ). We also note that the anchoring energy levels off above qA ∼ 3 (where q = 2π/ λ ), which suggests that increasing qA beyond a certain value does not provide any further advantage for the alignment of LCLCs. This finding provides a useful optimization criterion for the fabrication of the patterned cells to achieve stable monodomain alignment of LCLCs. Our analysis also explains why good alignment of LCLCs has been a difficult task.